Climate, pollution and grazing drive long‐term change in moorland habitats. Issue 2 (25th July 2016) - Britton, Andrea J.; Hester, Alison J.; Hewison, Richard L.; Potts, Jacqueline M.; Ross, Louise C.
Abstract: Question: Dwarf shrub moorland dominated by ericaceous plants is a distinctive, internationally important feature of northwest Europe, with its stronghold in Scotland. There have been major declines in its condition and extent. How has moorland composition changed within Scotland over the past ca. 35 yr and what is the role of climate change, pollution and grazing in driving these changes? Location: Five hundred and forty locations across Scotland, UK. Methods: We used a long‐term resurvey approach to assess change across Scottish moorlands. We relocated plots sampled ca. 35 yr previously in alpine heath, dry heath, wet heath and bog, and recorded vegetation species composition. We assessed change in species group richness and cover and mean Ellenberg values between surveys, using paired t ‐tests. We used CCA with variation partitioning and regression analysis to analyse the vegetation data with spatial data sets on climate, pollution and grazing, to assess the role of each driver in driving vegetation changes. Results: Significant diversity and compositional changes between surveys were found for all habitat types, particularly alpine heath. Significant associations were found with climate (many variables), pollution (N and S) and herbivore number (primarily deer). Species richness generally increased, but several specialist species declined in cover, especially those associated with higher altitude habitats (e.g. Arctostaphylos uva‐ursi, Salix herbacea and alpine lichens). Many of the most successful species are ubiquitous, e.g. the widespread grazing‐ and pollution‐tolerant graminoids Anthoxanthum odoratum, Juncus squarrosus, Festuca rubra and Nardus stricta and the generalist mosses Rhytidiadelphus squarrosus and Hylocomium splendens . Conclusions: Diversity and composition of moorlands in Scotland have changed significantly over the ca. 35‐yr period studied; the drivers of these changes are complex, with climate, pollution and grazing playing variable roles across habitats. The reduction in specialist species, homogenization of alpine heaths and declines in forb and lichen cover all represent negative changes in the biodiversity value of Scottish moorlands. Abstract : Dwarf‐shrub moorland is a distinctive feature of north‐west Europe. We used a long‐term resurvey to assess change in moorland composition across Scotland between the 1970s and 2005. Species richness of moorlands increased due to expansion of grazing and pollution tolerant graminoids and generalist mosses, while specialist species declined. Climate, pollution and grazing all played significant roles in driving these changes.